Transcriptomic change of human gingival cells during cultivation on gelatin composite hydroxyapatite and pig brain extract - Kantawong, Fahsai; Chaiyasert , Yasumin; Bungkhuan, Nichanun; Choocheep, Kanyamas; Kumsaiyai, Warunee; Wanachantararak, Penpitcha; Kuboki, Thasaneeya (Journal of Associated Medical Sciences, 2021)
Background: Biomaterials that contain mechanical and biochemical properties similar to neural tissue will provide the environment that support neuronal survival and development. Objectives: This study assessed the effects of three gelatin-based biomaterials on gene expression of primary human gingival fibroblasts. Materials and methods: Human gingival cells were cultured on 3 types of biomaterials; 10% gelatin, 10% gelatin with hydroxyapatite and 10% gelatin with hydroxyapatite and pig’s brain extract. These biomaterials were used in cell culture to investigate that they could support long-term culture of adult somatic cells like human gingival cell or not. Results: Human gingival cells were cultured on biomaterials for 21 days then, RNA sequencing showed up-regulation of 259 genes and down regulation of 210 gene in human gingiva cells cultured on Gel+HA+Brain compared to cells on tissue culture plates. RNA sequencing showed up-regulation of antioxidant genes, solute-carrier gene (SLC) superfamily, histone and cell cycle gene. Down-regulation of ECM and cytoskeletal protein were observed. The further study by reverse transcription real time – PCR was performed to confirm the result of Klf4, Tuj1, OCN, ACAN and VCAN gene expression in human gingival cells. Moreover, some neuronal related genes in human gingiva cells cultured on Gel+HA+Brain compared to cells on tissue culture plates were detected. Conclusions: The biomaterials (Gel+HA+Brain) affected gene expression in many aspects at 21 days culture. It was possible that 10% gelatin with nano-hydroxyapatite and pig’s brain extract could be used to support cell differentiation of the human gingival cells. In conclusion simple fabrication of the biomaterial from 10% gelatin with nano-hydroxyapatite and pig’s brain extract could be used for modulation of gene expression in adult somatic cells.